The Effectiveness of Full Day School System: The Elementary Students' Character through the Poll- Everywhere App - Muhammad Fihris Khalik; Fadhilla Sri Meutia; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
The full day school policy was the goal of the Full day School policy program expected by elementary schools is to intensify education factors in the school learning process one of the soft skill attributes expected of learning style in science education. The object of the study were elementary schools in the Ajatappareng area. The research locations were Enrekang regency, Sidenreng Rappang, Pinrang, Barru, and Parepare. The research method is qualitative research. The learning style of the concept of learning style is formed from birth. Some concepts are formed at pre-school age as prejudice. Simple experiments implemented into games and games have an important role in the formation of science concepts. Student learning styles in terms of the learning environment show of full day school that the majority prefers to study in a quiet environment; bright rooms; with cold temperatures; sit on a chair or soft pillow. Despite the fact that in terms quality education in realizing the golden generation through the concept of Islamic education and reflectively